Eris: Coordination-Free Consistent Transactions using Network Multi-Sequencing (Extended Version) - Li, Jialin; Michael, Ellis; Ports, Dan R. K. (University of Washington, 2017)
Distributed storage systems aim to provide strong consistency and isolation guarantees on an architecture that is partitioned across multiple shards for scalability and replicated for fault-tolerance. Traditionally, achieving all of these goals has required an expensive combination of atomic commitment and replication protocols – introducing extensive coordination overhead. Our system, Eris, takes a very different approach. It moves a core piece of concurrency control functionality, which we term multi-sequencing, into the datacenter network itself. This network primitive takes on the responsibility for consistently ordering transactions, and a new lightweight transaction protocol ensures atomicity. The end result is that Eris avoids both replication and transaction coordination overhead: we show that it can process a large class of distributed transactions in a single round-trip from the client to the storage system without any explicit coordination between shards or replicas. It provides atomicity, consistency, and fault-tolerance with less than 10% overhead – achieving throughput 4.5–35x higher and latency 72–80% lower than a conventional design on standard benchmarks.
XMLSEC '02 Proceedings of the 2002 ACM workshop on XML security